Phylogeographic Distribution of Human and Hare Francisella Tularensis Subsp. Holarctica Strains in the Netherlands and Its Pathology in European Brown Hares (Lepus Europaeus) - Miriam Koene; Jolianne Rijks; Miriam Maas; Robin Ruuls; Marc Engelsma; Peter van Tulden; Marja Kik; Jooske IJzer; Daan Notermans; Maaike de Vries; Ewout Fanoy; Ewout Fanoy; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Sequence-based typing of Francisella tularensis has led to insights in the evolutionary developments of tularemia. In Europe, two major basal clades of F. tularensis subsp. holarctica exist, with a distinct geographical distribution. Basal clade B.6 is primarily found in Western Europe, while basal clade B.12 occurs predominantly in the central and eastern parts of Europe. There are indications that tularemia is geographically expanding and that strains from the two clades might differ in pathogenicity, with basal clade B.6 strains being potentially more virulent than basal clade B.12. This study provides information on genotypes detected in the Netherlands during 2011–2017. Data are presented for seven autochthonous human cases and for 29 European brown hares (Lepus europaeus) with laboratory confirmed tularemia. Associated disease patterns are described for 25 European brown hares which underwent post-mortem examination. The basal clades B.6 and B.12 are present both in humans and in European brown hares in the Netherlands, with a patchy geographical distribution. For both genotypes the main pathological findings in hares associated with tularemia were severe (sub)acute necrotizing hepatitis and splenitis as well as necrotizing lesions and hemorrhages in several other organs. Pneumonia was significantly more common in the B.6 than in the B.12 cases. In conclusion, the two major basal clades present in different parts in Europe are both present in the Netherlands. In hares found dead, both genotypes were associated with severe acute disease affecting multiple organs. Hepatitis and splenitis were common pathological findings in hares infected with either genotype, but pneumonia occurred significantly more frequently in hares infected with the B.6 genotype compared to hares infected with the B.12 genotype.